2020
DOI: 10.3390/plants9111575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium Toxicity on Growth, Oxidative Damage, Antioxidant Defense System and Cadmium Accumulation in Two Sorghum Cultivars

Abstract: Heavy metal stress is a leading environmental issue reducing crop growth and productivity, particularly in arid and semi-arid agro-ecological zones. Cadmium (Cd), a non-redox heavy metal, can indirectly increase the production of reactive oxygen species (ROS), inducing cell death. A pot experiment was conducted to investigate the effects of different concentrations of Cd (0, 5, 25, 50, 100 µM) on physiological and biochemical parameters in two sorghum (Sorghum bicolor L.) cultivars: JS-2002 and Chakwal Sorghum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(44 citation statements)
references
References 60 publications
(71 reference statements)
6
36
0
2
Order By: Relevance
“…Cadmium stress-induced oxidative stress in pigeon pea was measured by the elevated contents of hydrogen peroxide, thiobarbituric acid reactive substances, and electrolyte leakage (Figure 2). Our findings are consistent with previous studies, where similar oxidative damage under cadmium exposure in other plant species has been reported [14][15][16].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Cadmium stress-induced oxidative stress in pigeon pea was measured by the elevated contents of hydrogen peroxide, thiobarbituric acid reactive substances, and electrolyte leakage (Figure 2). Our findings are consistent with previous studies, where similar oxidative damage under cadmium exposure in other plant species has been reported [14][15][16].…”
Section: Discussionsupporting
confidence: 94%
“…This boost in antioxidant enzymes in pigeon pea reflects the enzymatic mechanisms in response to cadmium-induced oxidative stresses. Previous studies have reported similar increases in antioxidant enzymes under Cd stress in other plant species [15,24,71].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Under heavy metal stress, plant cells produce ROS and gradually accumulate them, damaging the cell structure and slowing down plant growth (Hassan et al 2020). For this reason, the antioxidant system consisting of enzymes such as superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) in plants scavenges ROS to ensure normal plant growth (Shahid et al 2014).…”
Section: Discussionmentioning
confidence: 99%